Strategi Bermain Efektif: Stimulasi Psikologis Anak Melalui Pilihan Game yang Tepat - Cike Ilpia; Sri Kasih; Budiyanto; Mohammad Kanzunnudin; Indah Lestari; Mochamad Widjanarko (Pusat Riset dan Inovasi Nasional, 2025)
. This research examines Effective Play Strategies: Psychological Stimulation for Children Through Appropriate Game Choices, emphasizing the crucial role of play in shaping children's cognitive, emotional, and social development. Play is not merely entertainment; it serves as a laboratory where children experiment, develop skills, and form their personalities. The importance of aligning play types with a child's age-appropriate developmental stage is a primary focus, recognizing that each phase of psychological development has unique stimulation needs. The research method employed is a qualitative literature review, synthesizing information from various scholarly sources such as journals, books, and research reports. Literature searches were conducted systematically using relevant keywords in databases. The study results indicate that age-appropriate game selection is vital for optimizing a child's potential. Constructive play develops spatial understanding and problem-solving; role-playing facilitates empathy and social skills; while strategy games train logic and patience. In the digital era, balancing physical and digital play is crucial to ensure holistic development. In conclusion, play is a fundamental pillar in children's psychological development, and understanding effective play strategies empowers parents and educators to become facilitators guiding children toward balanced and optimal growth.